APPLICATION OF THE TALKING STICK LEARNING MODEL IN CREATING A FUN LEARNING ENVIRONMENT IN CLASS VII OF MTS MA'ARIF NU 09 KUTAWIS PURBALINGGA - Uswatun Khasanah; Muhamad Slamet Yahya (LP2M IAI Al-Khairat Pamekasan, 2026)
This article aims to analyze the effectiveness of implementing the Talking Stick learning model in creating a pleasant learning atmosphere in Grade VII of MTs Ma'arif NU 09 Kutawis Purbalingga. Conventional learning methods that tend to be teacher-centered often cause students to be passive and unmotivated. This qualitative research with a case study approach used data collection techniques of observation, interviews, and documentation. The results showed that the Talking Stick model was effective in increasing student participation, building positive interactions, and creating a more lively classroom atmosphere. The implications of this study highlight the importance of innovation in learning methods to develop students' potential holistically.